Undiscovered Potential in the Basement Exploring in Sumatra for oil and gas in naturally fractured and weathered basement reservoirs - Tako Koning; Nick Cameron; John Clure (Ikatan Ahli Geologi Indonesia, 2021)
This paper was first published in GEOExPro magazine, Vol. 18, No. 1, 2021, both in print and electronically (Koning et al., 2021) and is republished with permission from GEOExPro. For Berita Sedimentologi we have made various changes to the existing text and figures by including further results from our ongoing in-depth research into the geology of basement oil and gas plays in Sumatra.This paper provides and up-to-date and in-depth review of the status of exploration for oil and gas in naturally fractured and weathered basement throughout Sumatra. Also reviewed is the status of oil and gas production from Sumatra’s basement fields. In this paper’s section on Economic Impact, we emphasize the major positive contribution to Indonesia’s economy resulting from gas produced from basement reservoirs in the South Sumatra Basin.